Modified drift gill net (pakaroy) operation in Guimaras Strait an analysis of its effects to traditional fishing practices - Dela Torre, Rudy M. (University of the Philippines in the Visayas, 2002)
The study was conducted to determine the effects of pakaroy (modified drift gill net) on the operation of traditional fishing gears like pukot (gill net) and labay (long line), and the acceptability of using pakaroy among the fisherfolks in selected fishing communities of the Province of Guimaras. The date were obtained through personal interviews conducted on 24 respondents using a guided questionnaire which was translated to the local dialect. The results of the study reveal that the majority of respondents are sustenance fisherfolks, 67% are members of fisherfolk organizations, and 21% have been fishing in Guimaras Strait for more than 10 years. All the respondents own their fishing gears but only eight percent have constructed a pakaroy. The study also highlights the fact that 75% of the respondents concede that pakaroy is an excellent and very effective fishing gear compared to pukot and labay. However, 80% say that its operations adversely affect the operations of pukot and labay in th form of net/hook entanglement (90%) and encroachment of fisheing areas of pukot and (11%). There is also the issue on the pakaroy destroying fish habitat. The allegation that it is destructive to fish habitat can be open to dispute-pakaroy is operated in areas free of corals to avoid net damage. Furthermore, the Philippines Fisheries Code of 1998 (R.A. 8550) stipulates the three-cm. legal mesh size for nets; pakaroy nets are constructed with a mesh size largerthan three cm. A strong contention remains, however, in areas where the pakaroy drifts into areas where pukot or labay nets are also perating, specifically in areas without warning devices. hence, the encroachment issue appears to be a valid one.Despite the majority's stand tht pakaroy is destructive to fish habitat and adversely affects the fishing operation of other gears, almost 60% said that they prefer to put up pakaroy if given financial assistance. It is safe to conclude that economic considerations largely define the choice of fishing gears. The more effective a fishing gear is, the higher the volumes of fish catch, and the higher the income that will be derived. A cost-and-return analysis for these three fishing gears can help understand fisherfolks' preference and contribute worthwhile insights that may lead to the formulation of policies with regard to fishing gear operation, as well as to programs to assist fisherfolks that may be implemented i the future.Also, further research on the actual operation of pakaroy must be done to determine the merits or demerits of the contention thatit destroys fish habitat. A periodic stock assessment done every five years can serve as a good basis for regulations regarding the issuance of fishery licenses for specific fishing gears to beoperated in certain areas. Such regulation will then be embodied in a Municipal Fishery Ordinance. Regulations on the operation of different types of fishing gears can be givenconsiderations depending on the results of the stock assessment in order to observe the maximum sustainable yield (MSY) as prescribed under Section 8 of R.A. 8550. Zoningordinances on the proper utilization of the municipal waters can then be promulgated after thorough and in-depth study of the fishing areas using the results of stock assessment survey.